(untitled) (UNED Research Journal, 2016)
The white lipped peccary (Tayassu pecari) is a widely distributed Neotropical species that can be found from northern Argentina to southern Mexico. According to the IUCN, the white lipped peccary is vulnerable throughout its distribution range. In Costa Rica their distribution has decreased in 89%, its populations are in danger of extinction and are restricted to a few protected areas. This document presents the details of the first records of the presence of white lipped peccary in the Mixed National Wildlife Refuge of Caño Negro, where it was previously considered to be locally extinct. During 2013, 52 in depth interviews were conducted in several communities near the refuge. Between September and December 2015, eight camera traps were placed in farms close or within the refuge. In ten of the conducted interviews, people confirmed that there is a small population of these animals. Most people believe they live in a high and secluded sector of the refuge known as “Terrón”. Of the eight camera traps that were used, two were placed in this sector. One of these cameras registered a pack of white lipped peccary composed of at least eight individuals including adults and juveniles. Local ecological knowledge serves as a complement for technical knowledge and as a guide for planning and focusing efforts during the development of ecological research, such is the case of the present study. The confirmation of the presence of white lipped peccary is a finding of great importance since it can serve to increase the conservation measures that are applied in the refuge.